Online education: for a more inclusive and less unequal future - Covadonga Gijón; Fernando Fernández-Bonilla; Aurora Ruiz-Rua; Carlos Martínez-de-Ibarreta (International Telecommunications Society (ITS), 2024)
This paper examines the impact of online education on inclusivity and accessibility, focusing on undergraduate education. It explores how digital platforms address diverse learning needs and promote educational equity, particularly for students with disabilities. While online education offers personalized learning and enhanced engagement, it also highlights challenges such as digital literacy and access to reliable internet. The study addresses the digital divide, which disproportionately affects students from lower socioeconomic backgrounds, rural areas, and those with disabilities. The paper emphasizes the importance of policy interventions, institutional support, and the adoption of Universal Design for Learning (UDL) to create inclusive educational environments. It concludes by identifying gaps in empirical data and calling for further research to develop comprehensive approaches for equitable e-learning.
Keywords: 330; Online education; Digital divide; Inequality; e-learning; disabilities; higher education; Survey data; Econometric models